Analisis Motivasi ASN dalam Membayar Zakat Profesi pada Lingkup Dinas Pendidikan dan Kebudayaan Kabupaten Wajo - Mustika Ayu Safitri; Muzdalifah Muhammadun; Kaharuddin Kaharuddin; Suarning Suarning; Andi Bahri. S (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Zakat is an obligation and part of the pillars of Islam, an individual who has property that meets the nisab is required to pay zakat, one of the zakat, namely professional zakat, is believed to be able to make a positive contribution to society, especially the economic aspects of mustahiq. However, a person's motivation in paying zakat determines the effectiveness of zakat distribution. The aim of this research is to discuss and analyze the factors that influence the motivation of State Civil Servants (ASN) in paying professional zakat. This research uses a qualitative approach with a sample of 20 State Civil Apparatus (ASN) as informants. The research method involves observation, interviews, and data analysis using Nvivo 12 Plus software. The results of this research show that the motivation of State Civil Servants (ASN) in paying professional zakat is influenced by social, religious, ethical, and personal factors. Factors such as religious beliefs, moral values, and personal desires play an important role in ASN's decision to pay professional zakat. Apart from that, the social environment and religious knowledge also influence a person's awareness of paying zakat